Optimization Of Product Promotion Through Digital Marketing Content Training And Education For MSME Group Buildings, BUMDes Oeltua - Klaasvakumok J. Kamuri; Andrias U. T. Anabuni; Irience R. A. Manongga; Marianus S. Neno; Yonas F. Riwu; Yuri S. Fa’ah; Dominikus Kopong T. Aman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The existence of BUMDes becomes a hub of innovation and a platform for the village community to develop a profitable venture. BUMDes Nekaf Mese Oeltua village District of Kupang—NTT has been operating since 2017 and has several MSME groups built. Nevertheless, the facts show that a large group did not operate optimally and was even dissolved. These conditions indicate that the existence of the BUMDes Nekaf Mese village of Oeltua has not fully affected the improvement of the economy of the people. This is predicted by the limited knowledge, capabilities, and skills of the SDM, as well as the perception of marketing methods from a traditional perspective. It is important to carry out a program to improve the productivity of MSME groups through digital marketing content training and education in order to improve their competitive advantage. The results of this activity show a change in the participant's awareness of effective marketing methods in the modern marketing era. In addition, this activity enhances knowledge, abilities, and skills as a capital for business development and increases competitive advantage. As a reflection of these activities, we believe that it is necessary to collaborate with the various parties with their respective roles to contribute through long-term programs so as to create sustainability for the various efforts that have been made to enhance the growth of the existing MSME group. Keywords: Product Promotion; Digital Marketing; MSME; Household Economy